Dakwah Interaktif: Pergeseran dari Ceramah Satu Arah ke Diskusi Dua Arah - Santono, Agung Nugroho Reformis; Sukataman, Sukataman; Ni'am, Ahmad Miftahun; Chamdan, Umar (IAINU Kebumen, 2025)
The development of communication technology has driven a transformation in Islamic preaching from one-way sermons to two-way interactive discussions. This shift represents not only a change in medium but also in communication paradigm, positioning the audience as active participants in the delivery of religious messages. This study aims to analyze the characteristics of interactive da’wah using content analysis on digital platforms such as YouTube and TikTok. Employing a qualitative descriptive approach, this study examined 20 popular da’wah contents featuring preacher–audience interaction. The findings reveal that interactive da’wah emphasizes dialogical participation, spontaneous response, and the use of digital media as an open discussion space. This model enhances emotional engagement while shifting religious authority from a top-down to a participatory model. In conclusion, interactive da’wah represents a new form of Islamic communication adapted to the digital communication culture of modern society.